2009
DOI: 10.1007/s00114-009-0513-1
|View full text |Cite
|
Sign up to set email alerts
|

A contact sex pheromone component of the emerald ash borer Agrilus planipennis Fairmaire (Coleoptera: Buprestidae)

Abstract: Analyses of the elytral hydrocarbons from male and female emerald ash borer, Agrilus planipennis Fairmaire, that were freshly emerged vs. sexually mature (>10 days old) revealed a female-specific compound, 9-methyl-pentacosane (9-Me-C(25)), only present in sexually mature females. This material was synthesized by the Wittig reaction of 2-decanone with (n-hexadecyl)-triphenylphosphonium bromide followed by catalytic reduction to yield racemic 9-Me C(25), which matched the natural compound by gas chromatography/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 23 publications
2
89
0
Order By: Relevance
“…In particular, it is not always fully understood whether the CHC bouquet is perceived as a whole or whether single key components are sufficient alone or in combination to elicit a full behavioural response (Ginzel et al, 2003;Sugeno et al, 2006;Lacey et al, 2008;Silk et al, 2009). Recent studies on plant volatiles showed that key components of complex mixtures are often behaviourally active only in the presence of the natural odour background (Mumm and Hilker, 2005;Schroeder and Hilker, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is not always fully understood whether the CHC bouquet is perceived as a whole or whether single key components are sufficient alone or in combination to elicit a full behavioural response (Ginzel et al, 2003;Sugeno et al, 2006;Lacey et al, 2008;Silk et al, 2009). Recent studies on plant volatiles showed that key components of complex mixtures are often behaviourally active only in the presence of the natural odour background (Mumm and Hilker, 2005;Schroeder and Hilker, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, enantiomers of long-chain methylalkanes cannot be separated with state-of-the-art analytical tools, and thus the enantiomeric composition of these natural products still remains an open question (Hefetz et al, 2010;Millar, 2010). Consequently, although methylbranched CHCs have been identified as contact pheromones in some species (Sugeno et al, 2006;Ginzel et al, 2003;Lacey et al, 2008;Silk et al, 2009), it is unknown whether insects respond to these compounds stereoselectively (Hefetz et al, 2010), as is the case in many volatile insect pheromones (Mori, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many studies have been correlational only, showing statistically significant differences in the amounts and/or types of compounds present, without being able to confirm that any one or any group of these compounds do indeed have a signaling role. Other studies have bioassayed synthesized CHCs to probe the roles of specific compounds, with some success (15)(16)(17)(18)(19)(20)(21)(22). However, this approach is limited by the large number of compounds in CHC extracts so that a single study might require syntheses of numerous standards to assess the functional roles of all possible components.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl-branched cuticular hydrocarbons (MBCHs) have been identified or implicated as contact pheromones in a number of insect species (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), but most studies involving MBCHs have ignored the issue of stereochemistry and used only racemic MBCHs in bioassays to assess function. The linked questions as to whether insects biosynthesize MBCHs enantioselectively and whether insects can discriminate between the stereoisomeric Significance Methyl-branched hydrocarbons (MBCHs) are widely used for inter-and intraspecific communication by insects.…”
mentioning
confidence: 99%
“…Furthermore, a long range pheromone has not yet been detected for EAB [92]. Two short range, contact pheromones produced by adult emerald ash borer females have been identified that are antennally attractive to the males and have been used to improve trap captures [80,90,93,94]. Currently, key survey methods include the use of external signs and symptoms, green and purple sticky prism traps baited with ash volatile lures, green multi-funnel traps, trap logs, and using girdled trap trees which are an expensive and destructive method [15,88,92,95].…”
Section: Past and Present Detection Methods And Treatment Optionsmentioning
confidence: 99%